Monte Carlo simulation for prediction of worsening conditions of type-2 diabetes patients at peri-urban zones of lima city - Nieto Chaupis, Huber (2016)
From a sample of 1K type-2 diabetes cases, using Monte Carlo simulation and real data, we have estimated that a 2.5% might be potential candidates in being in the highest levels of progress of type-2 diabetes as manifested in nephropathy or necrosis, In addition, a 1 % of the sample might be highly sensitive to cardiovascular attack. The pattern of the sample is characterized by having low incomes per month, poor education to improve lifestyle, as well as the lack of contact with health specialist, among others. The results of this simulation might serve to reconfigure ongoing schemes of public health aiming to reduce diabetes complications and extend minimally the lifetime of those type-2 diabetes patients belonging to vulnerable groups.